Video Feature Perpaduan Budaya Candi Cetho sebagai Media Informasi - Nicholaus Wayong Kabelen; Fadila Fitra Mauludiah (Citradirga : Jurnal Desain Komunikasi Visual dan Intermedia, 2022)
Indonesia has an abundance of cultural diversity and historical heritage, one of which is cetho temple. This temple has an architecture similiar to the mayan buildings in mexico. The statues in this temple are not similar to the Javanese but are more similiar to the Sumerians. The andesite material used in Cetho Temple is different from the Hindu temple is different from the Hindu temples in the Majapahit kingdom which at that time were built using red bricks. The solution offered in this research is the creation of a feature video as a medium of information about the facts of syncretism found in the cetho temple. Cetho temple was built inthe period after the Hindu-Buddhist influence until the end of the adherents’ period. So that the architecture of the Cetho temple is still mixed with Hindu-Buddhist culture and also the local culture of the surrounding community. The selected sources are also in accordance with this research. Based on the questionnaire, the results of this study indicate that the public is able to understand the information from this feature video. This feature video has been well received by the public.